Manajemen Stres Di Masa Pandemi Covid-19 - Sri Nyumirah; Evin Novianti (AKPER Pasar Rebo, 2021)
The COVID-19 pandemic has a significant impact on people's mental health, therefore, monitoring and monitoring the mental health of the population during a crisis such as a pandemic is an immediate priority. The new Covid-19 pandemic has had a significant psychological and social impact on society. One of the psychological impacts that arise during this pandemic is stress, which if not overcome can interfere with life processes, so it is necessary to have the ability to overcome it by means of stress management. COVID-19 pandemic. The method used is a descriptive study. The author describes cases obtained from managed cases and explains the contents of the case, after being educated about the application of stress management that all respondents are 100% healthy (20) people. Stress management is done by physically relaxing, positive emotions, positive thoughts, positive behavior, positive relationships and spirituality, other forms that are carried out are by taking deep breaths, ensuring valid information, taking actions recommended by the government and increasing social support both with family and community surroundings.